2011
DOI: 10.1002/jmri.22699
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast‐enhanced four‐dimensional MR angiography for the evaluation of cerebral arteriovenous malformation: A preliminary trial

Abstract: Purpose: To prospectively evaluate noncontrast-enhanced (NCE), time resolved, four-dimensional (4D) magnetic resonance angiography (MRA) for assessment of cerebral arteriovenous malformation (AVM), with intraarterial digital subtraction angiography (DSA) performed as the reference standard. Materials and Methods:Fifteen patients (ten men, five women; age range 2-59 years, mean 29.4 years) with 15 untreated cerebral AVMs comprised the study population. NCE 4D MRA was performed on a 3.0 T MR scanner. MR images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…For clinical applications, acquisition with isotropic resolution over a large spatial coverage within 5 min is desired. bSSFP has been used in many NCE-MRA studies, mostly at 1.5T (8,(13)(14)(15)18,21,22,47,48) and few at 3T (19,49), owing to its high SNR efficiency and inherent flow-compensation capability. The challenges of 3T, including off-resonance artifacts and high SAR, have made bSSFP more preferable at 1.5T (50).…”
Section: Discussionmentioning
confidence: 99%
“…For clinical applications, acquisition with isotropic resolution over a large spatial coverage within 5 min is desired. bSSFP has been used in many NCE-MRA studies, mostly at 1.5T (8,(13)(14)(15)18,21,22,47,48) and few at 3T (19,49), owing to its high SNR efficiency and inherent flow-compensation capability. The challenges of 3T, including off-resonance artifacts and high SAR, have made bSSFP more preferable at 1.5T (50).…”
Section: Discussionmentioning
confidence: 99%
“…This modality has recently been tested clinically in the evaluation of intracranial collateral flow in patients with steno-occlusive diseases of brain-supplying arteries 20 . During the preparation of this manuscript, a similar study was conducted in 15 AVM patients, and the results showed that the consistency between non-contrast enhanced dMRA and DSA was excellent for the arterial feeders, good for the nidus size and moderate for the venous drainage 21 . Our data are consistent with the reported findings.…”
Section: Discussionmentioning
confidence: 96%
“…The relatively short bolus of labeled blood (∼1–2 sec) is a major limiting factor of 4D MRA and potentially hampers its clinical utility, especially at 1.5T and 3T. For instance, it remains a challenge to capture draining veins in AVM, which usually appear in later phases of dynamic MRA (after 1–2 sec) …”
mentioning
confidence: 99%
“…For instance, it remains a challenge to capture draining veins in AVM, which usually appear in later phases of dynamic MRA (after 1-2 sec). 12,13 Recently, technical advances in both hardware and software of high-field MRI has enabled 7T MRI systems to become commercially available for human study. A number of MRI techniques, 3D anatomical and angiographic sequences in particular, have been developed and optimized at 7T to enable high-resolution acquisition by making use of the increased signal-to-noise ratio (SNR) at ultrahighfield.…”
mentioning
confidence: 99%